RETRACTED: How college freshmen increase their academic self-efficacy? An indigenous approach - Sutarmanto, Hadi (Psychological Research and Intervention, 2018)
RETRACTEDFollowing rigorous and careful concerns and consideration in the review of the article published in Psychological Research and Intervention journal entitled “How college freshmen increase their academic self-efficacy? An indigenous approach” Vol 1, No 2, pp. 50-56, 2018, DOI: http://dx.doi.org/10.21831/pri.v1i2.21858This paper has been found to violate the principles of Psychological Research and Intervention journal publication and has been retracted.The article has contained redundant material and throughout a careful examination, the editor has found that the paper has also been published in Indigenous and Cultural Psychology Working Paper Series Volume 13, Issue 2, Article No. 2, December 2017, which can be accessed at https://simpan.ugm.ac.id/s/yrOaQS9IrHYE2C0#pdfviewerThe document and its content have been removed from Psychological Research and Intervention journal and reasonable effort should be made to remove all references to this article.